Filozofia analityczna a metoda fenomenologiczna - Czerniawski, Jan (Filozofia Nauki, 2000)
This paper is a reply to Jan Wolenski's polemics (Filozofia Nauki 1/2000) against the author's essay „On the Epistemic Impotence of Analytical Philosophy” (Filozofia Nauki 3-4/1998). The author expresses his conviction that it is in analytical philosophy that the most interesting - and at the same time well-established - cognitive results have been reached, but many of these results have been obtained, not thanks to the declared semantic method, but thanks to the phenomenological method, which have been used at least unconsciously. Therefore the gap between phenomenology and analytical philosophy is not so huge as it might seem at first glance.